2020
DOI: 10.1038/s41467-019-13771-5
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 mediates survival of ALK-rearranged lung cancer cells treated with alectinib via pro-apoptotic protein regulation

Abstract: Despite the promising clinical efficacy of the second-generation anaplastic lymphoma kinase (ALK) inhibitor alectinib in patients with ALK-rearranged lung cancer, some tumor cells survive and eventually relapse, which may be an obstacle to achieving a cure. Limited information is currently available on the mechanisms underlying the initial survival of tumor cells against alectinib. Using patient-derived cell line models, we herein demonstrate that cancer cells survive a treatment with alectinib by activating Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 67 publications
3
57
0
1
Order By: Relevance
“…The YAP1/Hippo signaling pathway was closely associated with GC progression, and YAP1induced dysregulation of Hippo pathway contributed to cancer development [36]. According to the previous data, YAP1 served as an oncogene in GC, and targeting YAP1 was effective to restrain cancer progression [37][38][39], which were supported by our data that YAP1 was high-expressed in GC tissues and cells, and GC patients with high-expressed were prone to have a worse prognosis. In addition, recent data hinted that YAP1 could be epigenetically silenced by its upstream miRNAs [48,49], and we surprisingly evidenced that miR-16-5p targeted the 3 UTR of YAP1 mRNA for its inhibition and degradation.…”
Section: Discussionsupporting
confidence: 77%
“…The YAP1/Hippo signaling pathway was closely associated with GC progression, and YAP1induced dysregulation of Hippo pathway contributed to cancer development [36]. According to the previous data, YAP1 served as an oncogene in GC, and targeting YAP1 was effective to restrain cancer progression [37][38][39], which were supported by our data that YAP1 was high-expressed in GC tissues and cells, and GC patients with high-expressed were prone to have a worse prognosis. In addition, recent data hinted that YAP1 could be epigenetically silenced by its upstream miRNAs [48,49], and we surprisingly evidenced that miR-16-5p targeted the 3 UTR of YAP1 mRNA for its inhibition and degradation.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the morphological changes of the McF-7 breast cancer cells cultured in the presence of matrine also revealed its cytotoxic effect on McF-7 cells. apoptosis induction serves a key role in cancer therapy (35). in the present study, Hoechst 33342 staining and flow cytometry revealed that matrine could cause cellular apoptosis in McF-7 cells.…”
Section: Discussionsupporting
confidence: 56%
“…The proteins in the sample were subjected to tandem mass tag-labeling proteomic analysis, according to previously described methods ( Tsuji et al, 2020 ). Proteins were identified by MASCOT search against the S. vesiculosa HM13 protein database.…”
Section: Methodsmentioning
confidence: 99%